2015
DOI: 10.4187/respcare.03652
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complications in Stroke Subjects Undergoing Early Versus Standard Tracheostomy

Abstract: BACKGROUND: Although the benefits of early tracheostomy have been discussed in numerous studies, it is still unclear whether it is safe to perform early tracheostomy on unstable stroke patients. The purpose of this study is to assess the influences of the timing of tracheostomy on the incidence of complications following surgical tracheostomy in stroke patients. METHODS: We retrospectively performed chart reviews of 95 stroke subjects who underwent tracheostomy. In terms of timing, procedures performed within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…Seder et al found very low tracheostomy-related complications rates (9% with ST and 8% with PT) (8). Other studies found between 19 and 25% tracheostomy-related complications rates in stroke patients (15,16). In our study, tracheostomy-related complications rates were 24.6% (21.1% with PT, and 29.6% with ST).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Seder et al found very low tracheostomy-related complications rates (9% with ST and 8% with PT) (8). Other studies found between 19 and 25% tracheostomy-related complications rates in stroke patients (15,16). In our study, tracheostomy-related complications rates were 24.6% (21.1% with PT, and 29.6% with ST).…”
Section: Discussionsupporting
confidence: 46%
“…For critically ill patients, the recommended standard method for tracheostomy is bedside PT, or ST when PT is anatomically not applicable (7). The advantages of PT include short procedure time at bedside, lesser tracheostomy complications such as stoma infection or bleeding, and less tissue damage due to minimal dissection (15). In our study, we found that ST was more preferred between 2009-2011, whereas PT increased during the later years.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Various observational studies in neurocritical patients suggested that earlier tracheostomy is associated with improved clinical outcome and reduced hospital stay. [ 4 ] It is still unclear whether and when ventilated patients with ischemic or hemorrhagic stroke should obtain a tracheostomy, and to recognize the need to tracheostomize these patients is a daily dilemma. This prospective study aims to assess the benefits of early tracheostomy in neurocritical patients on ventilator in terms of ICU-LOS (ICU-LOS), number of days on ventilator (ventilator days), incidence of ventilator-associated pneumonia (VAP), and mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…Auf den rehabilitativen Verlauf wirken sich vor allem Spätkomplikationen wie Stenosen und Tracheomalazien, die nicht selten erst nach Dekanülierung manifest werden, sowie die Bildung von die Atmung beeinträchtigenden Granulationen und Granulomen aus [20,22,27,45,66]. Arrosionsblutungen werden meist durch intratracheales Absaugen hervorgerufen und weisen häufig auf eine Fehllage der TK hin (abb.…”
Section: Komplikationenunclassified